Institutional aspects of agricultural research organization in Latin America, problems, perspectives and policy issues - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
38 páginas